Audit Fee Premium for Industry Specialization: A Developed Country Perspective - Muhammad Shahin Miah (Journal of Accounting, Business and Management (JABM), 2019)
This paper examines the effects of industry specialization (city-level, nationallevel, and joint-level) on audit pricing in the Australia. By using Australian Stock Exchange (ASX) listed companies, this study documents that auditors who are industry specialists at both city-and national-level charge significantly higher audit fees compare to those auditors who are specialists either only at city-level or only at national-level industry specialist. However, in further analysis, this study documents that firms who are city-level industry specialists they charge relatively higher audit fees than nationallevel industry specialists, which is consistent with prior research on audit fee premiums studies concentrated in Australia. The greater audit fees charged by city-level industry specialists auditors are possibly attributed to recent changes in accounting regulations environment in Australia (e.g., mandatory adoption of IFRS). Such a significant shift in financial reporting environment due of IFRS adoption can affect audit expertise which may be reflected in this study. This study findings are robust in a set of alternative tests following prior research.